Debt, temporality and morality: Process of subjectivation of young professional couples - Lorena Pérez-Roa; Trabajo Social, Universidad de Chile, Santiago, Chile; Centro Núcleo Milenio Autoridad y Asimetrías de Poder.; Matías Gómez Contreras; Instituto de Sociología, Pontificia Universidad Católica de Chile; Becario Centro de Estudios de Conflicto y Cohesión Social (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
This article discusses how different types of credits and debt relationships generate subjectivation processes in young Chilean professionals. For this purpose, 34 semi-structured interviews were analyzed with young couples from Santiago and the great Concepción. Two findings are presented: the way in which debt acts as a device for capturing present and future actions, organizing the time of the subjects; how credit generates not only economic but also moral debts, which are linked to socially created expectations and for which the subjects feel individually responsible. It is concluded that the intrusion of credits as a permanent element in the background of daily life displaces the conflictive situation of indebtedness towards the condition of arrears. This causes, on the one hand, the construction and limitation of present and future projects to have latent avoidance of arrears, while, on the other hand, it shifts moral debts towards the relations and social commitments that motivate the acquisition of financial liabilities.